(untitled) (AACINI - International Journal of Industrial Engineering, 2022)
At the II International Women’s Day (II JIM), within the framework of the International Congress of Industrial Engineering and related careers (XIV COINI 2021), a discussion was proposed to address a current issue as complex and relevant as the adaptation of study plans based on the new standards; and specifically in the career of industrial engineering. In this sense, different women protagonists of institutional management were invited to participate in the discussion; at a national and international level, to know their vision on the matter. This allowed sharing and socializing the challenges of adapting study plans and new standards for industrial engineering careers, addressing three axes: Adaptation of Study Plans, with a view to the 2030 graduate, Vocations and women in engineering and A international level career. It is concluded that the discussion has generated a discussion kick of such a relevant topic and a basis to continue debating in the future.